Answer: Multiply (60 − 2x) and (2 + 0.25x) to create the equation y = -0.5x2 + 11x + 120
We know that David wants to increase the price per cup to increase his revenue. He found out that for every $0.25 grows( increase), x, in the price for each cup.
In the event of a price increase, 2 cups remain unsold, and doubling the cups is still not sold. Then the numbers are sold (60-2x). Depending on the choice:
Revenue= (60 -2x)(2 +0.25x)
60·2 +60·0.25x -2x·2 -2x·0.25x
= -0.5x² +11x +120
Answer:
Multiply (60 − 2x) and (2 + 0.25x) to create the equation y = -0.5x2 + 11x + 120
Step-by-step explanation:
Here, x represents the times at which the price is increased,
Since, the original price of one cup = $ 2,
So, after increasing x times of $ 0.25, the new price of each cup = 2 + 0.25x,
Also, the original number of mochas = 60,
Given,
With increasing the price $ 0.25, x times, the number of cup is decreased by 2 times of x,
That is, the new number of mochas = 60 - 2x
Hence, the total revenue would be,
y = new price of each cup × new number of mochas
⇒ y = (2 + 0.25x)(60 - 2x)
⇒ y = 120 - 4x + 15x - 0.5x²
⇒ y = -0.5x² + 11x + 120
He can find find the equation which represents his daily revenue, by Multiplying (60 − 2x) and (2 + 0.25x) to create the equation y = -0.5x² + 11x + 120
Find the x intercepts of thr following parabola y= -4x^2 + 8x +12
Answer:
x=-1 or x=3
Step-by-step explanation:
This is a quadratic equation
You can use the graph tool to visualize the x-intercepts on the graph as attached below.
x=-1 or x=3
For this case we must find the x-intersepts values of the following equation:
[tex]y = -4x ^ 2 + 8x + 12[/tex]
Doing y = 0 we have:
[tex]0 = -4x ^ 2 + 8x + 12[/tex]
Dividing between -4 on both sides of the equation:
[tex]x ^ 2-2x-3 = 0[/tex]
We factor, we look for two numbers that when multiplied by -3 and when added by -2. These are -3 and 1:
[tex]-3 + 1 = -2\\-3 * 1 = -3\\(x-3) (x + 1) = 0[/tex]
Thus, the x-intercepts values are:
[tex]x_ {1} = 3\\x_ {2} = - 1[/tex]
Answer:
[tex]x_ {1} = 3\\x_ {2} = - 1[/tex]
Consider a Poisson distribution with an average of three customers per minute at a local grocery store. IF X = the number of arrivals per minute, find the probability of more than 7 customers arriving within a minute.
Answer:
0.012
Step-by-step explanation:
The probability of more than 7 customers arriving within a minute is obtained by taking the probability at X equal to 0, 1, 2, 3, 4, 5, 6, and 7 then subtracting from the total probability. It can be expected about 1.2% of times that more than 7 customers arriving within a minute.
Answer: 0.0216
Step-by-step explanation:
Given : Average arrivals of customers at a local grocery store = 3 per minute
The Poisson distribution formula :-
[tex]\dfrac{e^{-\lambda}\lambda^x}{x!}[/tex], where [tex]\lambda[/tex] is the mean of the distribution.
If X = the number of arrivals per minute, then the probability of more than 7 customers arriving within a minute will be :-
[tex]\dfrac{e^{-3}(3)^7}{7!}=0.0216040314525\approx0.0216[/tex]
Hence, the probability of more than 7 customers arriving within a minute = 0.0216
Two scientists are running experiments testing the effects of a vaccine on different control groups. The results are shown in the graph using the functions f(x) and g(x): Which statement best describes the graph of f(x) and g(x)?
A- The graph of g(x) will eventually exceed the graph of f(x)
B- The graph of f(x) will eventually exceed the graph of g(x)
C- The graphs will both have their y-intercept equal to 5
D- The graphs will both have their y-intercept equal to 2
PLEASE HELP ME!!!!
Answer: I believe the answer is B.
Although, if the answer to this question isn't B, it should defiantly be C.
Answer:
The correct option is B.
Step-by-step explanation:
The graph of f(x) is g(x) is given.
Graph of both functions intersect each other at a point. Before the point of intersection g(x)>f(x) and after the point of intersection g(x)<f(x).
The graph of f(x) will eventually exceed the graph of g(x). Therefore the correct option is B.
Function g(x)<f(x) for the large value of x, So option A is incorrect.
From the given graph it is clear that the y-intercept of f(x) is 0.2 and y-intercept of g(x) is 2.
So, option C and D are incorrect.
multiply 5x^2-6x+2 4x^2-3x
Answer:
[tex]20x^{4}-39x^{3} +26x^{2}-6x\\[/tex]
Step-by-step explanation:
Multiply the two polynomials by multiplying each term
[tex](5x^{2} -6x+2)(4x^{2} -3x)\\5x^2*4x^2+5x^2(-3x)+(-6)*4x^2+(-6x)(-3x)+2*4x^2+2(-3x)\\20x^{4}-39x^{3} +26x^{2} -6x\\[/tex]
To multiply the given expressions, use the distributive property and combine like terms. The final result is 20x⁴ - 39x³ + 26x² - 6x.
Explanation:To multiply the expression (5x²-6x+2) (4x²-3x), we can use the distributive property. Multiply the first term in the first binomial (5x²) by each term in the second binomial (4x², -3x), and then multiply the second term in the first binomial (-6x) by each term in the second binomial. Finally, multiply the third term in the first binomial (2) by each term in the second binomial. Combine like terms and simplify as needed to get the final result.
Applying this process, we get:
5x² × 4x² = 20x⁴
5x² × -3x = -15x³
-6x × 4x² = -24x³
-6x × -3x = 18x²
2 × 4x² = 8x²
2 × -3x = -6x
Combining all the terms, we have:
20x⁴ - 15x³ - 24x³ + 18x² + 8x² - 6x
Simplifying further, we get:
20x⁴ - 39x³ + 26x² - 6x
Learn more about the Multiplication of Polynomials here:https://brainly.com/question/34232638
#SPJ11
Last week Rachel power walked 2 miles per day on each of the 7 days. During the
same week, she also jogged 5
miles per day on 4 days. What was the total number of
miles Rachel power walked and jogged last week?
Answer: 34 miles
Step-by-step explanation:
First multiply the 2 miles she power walked by the 7 days. (14 miles)
Next, multiply the 5 miles by the 4 days. (20)
Add both numbers, 20+14=34 miles
What is the radius and diameter of the following circle?
Answer:
r = 4.2 cm; d = 8.4 cm
Step-by-step explanation:
The radius is the distance from the centre of the circle to the circumference.
r = 4.2 cm
The diameter is the length of a straight line that passes through the centre with each end at the circumference.
d = 2r = 2 × 4.2 cm = 8.4 cm
Answer:
radius=4.2
diameter=8.4
Step-by-step explanation:
Last week Holly took a math test. She got 98 out of 123 question correct. What percentage did Holly get correct?
Answer:
79.67479675 %
Step-by-step explanation:
To find the percentage take the correct amount over the total amount, then multiply by 100
98/123 * 100
79.67479675 %
Answer:
the answer is 79.64%
Step-by-step explanation:
A/B=P/100
98/123=p/100
9800/123=123p/123
p=79.64%
[tex]( - x + 3) - (4x - 10)[/tex]
Answer:
-5x+13 given (-x+3)-(4x-10)
Answer:-5x+13
Step-by-step explanation:
We are going to distribute to get rid of the ( ):
-x+3-4x+10
Pair up like terms:
-x-4x+3+10
Combine the like terms:
-5x+13
Answer:
-5x+13
Step-by-step explanation:
( - x + 3) - (4x - 10)
Distribute the minus sign
( - x + 3) - 4x + 10
Combine like terms
-5x +13
After traveling steadily at 400 meters above a shipwrecked hull, a submerged vessel starts to descend when its ground distance
from the hull is 7 kilometers. What is the angle of depression for this part of the travel?
Select one
O a 1.00
6.327
C 86.73
d. 88.00
Answer:
im trying to find this answer too dont worry :(
Step-by-step explanation:
I dont know
Answer:
Option B, [tex]3.27[/tex]
Step-by-step explanation:
Given -
The submerged vessel travel horizontal distance above the shipwrecked hull
[tex]= 400[/tex]
[tex]= 0.4[/tex] kilometers
The vertical distance from the the shipwrecked hull to the ground is equal to [tex]7[/tex] kilometers
There forms a right angled triangle with
Base [tex]= 7[/tex] kilometer
Perpendicular [tex]=[/tex] 0.4 kilometer
Tan (angle) [tex]= \frac{Perpendicular}{Base}[/tex]
Substituting the given values we get -
Angle of depression
[tex]= tan^{-1}(\frac{0.4}{7})\\= 3.27[/tex]
Hence, option B is correct.
(5 x 2)(10^20)^5
what is the answer
Answer:
5 x 2 = 10
(10^20)^5 = 10^100
(10) x (10^100) = 10^101 which is 1 followed by 101 zeroes.
Answer:
10 ^101
Step-by-step explanation:
(5 x 2)(10^20)^5
5*2 = 10
We know a^b^c = a^(b*c)
(10^20)^5 = 10 ^ (20*5) = 10 ^ 100
10 * 10^100
Replacing 10 with 10^1
10^1 * 10^100
We know that a^b * a^c = a^ (b+c)
10^1 * 10^100 = 10 ^(100+1) = 10 ^101
You are a pharmacy technician. You need to prepare a 0.85-gram dose of a liquid antibiotic. The medicine is concentrated at 250 milligrams of antibiotic per 5 milliliters of liquid. How many milliliters should you pour into a prescription bottle?
Answer:
17mL
Step-by-step explanation:
Convert 0.85 gr to miligrams
If 100 mg is 1 gr. Then, 0.85 gr is 850 mg
So, 850 multiply for 5ml and divide for 250 ml
or [tex]850mg \frac{5ml}{250mg}[/tex]
So all mg is gone and the amount of mililiters is 17
Answer:
17 milliliters of dose should be poured into a prescription bottle.
Step-by-step explanation:
Amount of dose in liquid antiboitic = 0.85 g = 850 mg
1 g = 1000 mg
Concentration of antibiotic = 250 mg/5 ml = 50 mg/mL
So, in 1 mL of liquid we have 50 mg of antibiotic.
Then in 0.85 mg of antibiotic will be:
[tex]\frac{1}{50}\times 850 mL=17 mL[/tex]
17 milliliters of dose should be poured into a prescription bottle.
graph the equations to solve the system
y=-x
y=2x+3
click on the correct answer #1 solutions :all numbers on the line #2 no solutions {} #3 one solution:{-1,1} #4 one solution:{0,3}
Answer:
This system has one solution (-1,1)
Step-by-step explanation:
The attached picture shows the solutions for the system
If we equalize the eq. obtain the following
-x=2x+3
From we obtain that x= -1
Using the first equation y=-x, we obtain that y=1
so (-1,1)
Which value of ris a solution to this equation?
21 + 3r = 48
Answer:
r= 9
Step-by-step explanation:
;/
The solution to the equation 21 + 3r = 48 is r = 9.
What is an equation?An equation is a mathematical statement that is made up of two expressions connected by an equal sign.
Example:
3x + 5 = 9 is an equation.
We have,
21 + 3r = 48
Subtract 21 on both sides.
3r = 48 - 21
3r = 27
Divide both sides b 3.
r = 9
Thus,
The value of r is 9.
Learn more about equations here:
https://brainly.com/question/17194269
#SPJ2
Evaluate j/4 when j =12
thats easy it is 4
Hope this helps:)
tate the order and type of each transformation of the graph of the function
ƒ(x) = –(x + 1)3 + 1 as compared to the graph of the base function.
right 1 unit, reflection about the x-axis, up 1 unit
left 1 unit, reflection about the y-axis, up 1 unit
left 1 unit, reflection about the x-axis, up 1 unit
left 1 unit, up 1 unit, reflection about the x-axis
Answer:
left 1 unit, reflection about the x-axis, up 1 unit
Step-by-step explanation:
This is a cubic that has been moved left 1 unit because of the (x+1)^3 part.
It also has been moved up one unit because of the plus 1 on the outside of the cube.
There has also been a reflection across the x-axis because of the -1 in front of the -(x+1)^3 part.
In general, g(x-h)+k means:
1) the function g has been moved right (if h is positive) or moved left (if h is negative).
2) the function g has been moved up (if k is positive) or down (if k is negative)
The table shows conversions for common units of capacity.
Units of Capacity
Customary System Units
Metric System Units
1 gallon
3.79 liters
1 quart
0.95 liters
1 cup
0.24 liters
How many quarts are in 583.7 liters? Round to the nearest tenth.
There are 138.6 quarts in 583.7 liters.
There are 153.6 quarts in 583.7 liters.
There are 554.5 quarts in 583.7 liters.
There are 614.4 quarts in 583.7 liters.
Answer:
Option D is correct.
Step-by-step explanation:
We need to find that how many quarts are there in 583.7 liters.
From conversion table we geet,
1 quart = 0.95 liters
=> 1 liters = 1/0.95 quarts
=> 1 liters = 1.0526 quarts
I liter has 1.0526 quarts then 583.7 liters will have:
583.7 liters = 1.0526*583.7 quarts
583.7 liters = 614,4 quarts.
So, Option D There are 614.4 quarts in 583.7 liters. is correct.
Answer:
d
Step-by-step explanation:
4^(4x-1)=32
How do I solve this problem? Do I do 4 to the fourth power first?
Answer:
[tex]\large\boxed{x=\dfrac{7}{8}}[/tex]
Step-by-step explanation:
[tex]4^{(4x-1)}=32\\\\(2^2)^{4x-1}=2^5\qquad\text{use}\ (a^n)^m=a^{nm}\\\\2^{2(4x-1)}=2^5\iff2(4x-1)=5\ \ \text{use the distributive property}\ a(b+c)=ab+ac\\\\(2)(4x)+(2)(-1)=5\\\\8x-2=5\qquad\text{add 2 to both sides}\\\\8x=7\qquad\text{divide both sides by 8}\\\\x=\dfrac{7}{8}[/tex]
Find the domain of the following piece wise function
Answer:
[-4, 6)Step-by-step explanation:
[tex]f(x)=\left\{\begin{array}{ccc}x+4&if&-4\leq x<3\\2x-1&if&3\leq x<6\end{array}\right\\\\\text{The domain of a function is a set of x's}.\\\\\text{We have}\\\\-4\leq x<3\to x\in[-4,\ 3)\\3\leq x<6\to x\in[3,\ 6)\\\\\text{The domain:}\ [-4,\ 3)\ \cup\ [3,\ 6)=[-4,\ 6)[/tex]
Find the equation of the line through ( - 10, - 8) that is perpendicular to the line through (10,6), (5,5).
The equation is
(Be sure to enter your answer as an equation)
Preview
Answer:
y=-5x-58
Step-by-step explanation:
The equation of a line in slope-intercept form is y=mx+b where m is the slope and b is the y-intercept.
Perpendicular lines have opposite reciprocal slopes.
Anyways we need to find the slope of the line going through (10,6) and (5,5).
To find the slope, we are going to line up the points vertically and subtract vertically, then put 2nd difference over 1st difference. Like so:
( 10 , 6)
- ( 5 , 5)
------------------
5 1
So the slope of the line through (10,6) and (5,5) is 1/5.
The slope of a line that is perpendicular will be the opposite reciprocal of 1/5.
The opposite reciprocal of 1/5 is -5.
The line we are looking for is y=-5x+b where we need to find the y-intercept b.
y=-5x+b goes through (-10,-8)
So we can use (x,y)=(-10,-8) to find b in y=-5x+b.
y=-5x+b with (x,y)=(-10,-8)
-8=-5(-10)+b
-8=50+b
Subtract 50 on both sides:
-8-50=b
-58=b
So the equation is y=-5x-58
Which statement about the transformation is true A) it is isometric because side length are the same B) Isometric because angle measures are the same C) not isomeric because side lengths not same D) not isometric cuz angle measures not same
Answer:
C) not isomeric because side lengths not same
Step-by-step explanation:
Isometric means that the lengths are preserved after rotation or transformation.
As we can see in the given figures that the lengths of sides of the original figure and transformed figure are are not same which means the lengths are not preserved.
So the correct answer is:
C) not isomeric because side lengths not same ..
Option: C is the correct answer.
C) Not isomeric because side lengths not same.
Step-by-step explanation:Isometry--
It is a transformation which preserves the length of the original figure i.e. it is a distance preserving transformation.
Two figures are said to be isometric if they are congruent.
By looking at the figure displaying the transformation we observe that the size of the original figure is changed.
i.e. the figure is dilated by a scale factor of 2 , since each of the sides of the polygon which is a trapezoid is increased by a factor of 2.
Hence, the transformation is not an isometry.
table:
x c(x)
(days) (dollars)
1. 25
2. 45
3. 60
4. 70
Answer:
2) Yes, each x-coordinate is only used once.
3) {1,2,3,4}
4) {25,45,60,70}
5) (3,60)
6) No because (4,7) and (4,25) share the same x-coordinate.
Step-by-step explanation:
A relation is a function if there is no more than one y-value assigned to an x.
Any x used can only be used once in an order pair.
You that here.
(1,25)
(2,45)
(3,60)
(4,70)
So basically because all of the x-coordinates are different, this is a function.
The domain is the x-coordinate of each pair (the first of each pair):
{1,2,3,4}.
The range is the y-coordinate of each pair (the second number of each pair):
{25,45,60,70}.
One ordered pair that I see in the table is (3,60). There are 3 others you can choose and I named them above.
{(4,10),(3,15),(1,5),(2,25),(4,25)} is not a function because there are more than one pairs with the same x-coordinate,4.
Which is a horizontal asymptote of this function?
Answer:
C
Step-by-step explanation:
When both the numerator and denominator of a rational function have the same degree, you divide the highest powered term's coefficients. That is the horizontal asymptote.
Since this function has third degree in both the numerator and denominator, we divide the respective coefficients to find the horizontal asymptote.
So, y = 9/7
Correct answer is C
Note: horizontal asymptote is always in the form y = a (where a is the constant)
Khaled bought 32 cups of juice to distribute to his students. He decided to drink 2 cups himself and pour each of his students 1.25 cups. How many of his students received juice?
Answer:
24 students
Step-by-step explanation:
So we started with 32 cups of juice.
Kahled drunk 2 cups so (32-2)=30 cups is left.
If x represents the number of students he receive juice and each student gets the same amount of juice which is 1.25 cups, then we have the equation
1.25x=30 to solve for x.
Divide both sides by 1.25:
x=30/1.25
x=24
24 students receive juice
ABCD is a rectangle. What is the value of X?
Answer:
x = 33 mStep-by-step explanation:
Use the Pythagorean theorem:
[tex]leg^2+leg^2=hypotenuse^2[/tex]
We have
[tex]leg=56\ m,\ hypotenuse=65\ m,\ leg=x\ m[/tex]
Substitute:
[tex]56^2+x^2=65^2[/tex]
[tex]3136+x^2=4225[/tex] subtract 3136 from both sides
[tex]x^2=1089\to x=\sqrt{1089}\\\\x=33\ m[/tex]
Answer:
33
Step-by-step explanation:
We need to use the Pythagorean Theorem.
65 is the length for the hypotenuse.
So we do a^2+b^2=c^2 where a and b are legs and c is the hypotenuse.
x^2+56^2=65^2
x^2+3136=4225
Subtract 3136 on both sides
x^2 =1089
Square root both sides
x=33
The answer is 33 meters.
what is the squae root of -16
Answer:
4i
Step-by-step explanation:
sqrt(-16)
We know the sqrt (ab) = sqrt(a) sqrt(b)
sqrt(-16) = sqrt(16) sqrt(-1)
We know that the sqrt(-1) = i
= 4i
Answer:
4i
Step-by-step explanation:
sqrt(-16)
We know the sqrt (ab) = sqrt(a) sqrt(b)
sqrt(-16) = sqrt(16) sqrt(-1)
We know that the sqrt(-1) = i
= 4i
5.
Find the limit of the function by using direct substitution. (6 points)
limit as x approaches zero of quantity x squared minus three.
3
Does not exist
-3
0
6.
Find the limit of the function by using direct substitution. (6 points)
limit as x approaches three of quantity x squared plus three x minus one.
17
0
-17
Does not exist
7.
Find the limit of the function algebraically. (6 points)
limit as x approaches four of quantity x squared minus sixteen divided by quantity x minus four.
Does not exist
4
1
8
8.
Find the limit of the function algebraically. (6 points)
limit as x approaches zero of quantity x squared minus two x divided by x to the fourth power.
Does not exist
8
0
-8
Finding limits by direct substitution means simply means to evaluate the function at the desired value: in the first case, we have to evaluate [tex]f(x)=x^2-3[/tex] at [tex]x=0[/tex]: we have
[tex]f(0)=0^2-3 = 0-3=-3[/tex]
Similarly, in the second example, we have
[tex]f(x)=x^2+3x-1 \implies f(3) = 3^2+3\cdot 3-1 = 9+9-1 = 17[/tex]
Going on, we have
[tex]f(x) = \dfrac{x^2-16}{x-4} = \dfrac{(x+4)(x-4)}{x-4} = x+4[/tex]
And thus we have
[tex]f(4) = 4+4=8[/tex]
Finally, we have
[tex]f(x) = \dfrac{x^2-2x}{x^4} = \dfrac{x(x-2)}{x^4} = \dfrac{x-2}{x^3}[/tex]
So, we can't evaluate this function at 0.
The limits of the functions are determined and the values are:
5) -3
6) 17
7) 8
8) does not exist.
Given data:
5)
The limit function is expressed as [tex]\lim_{x \to 0} (x^{2} -3)[/tex].
So, when x = 0, the limit is:
L = 0² - 3
L = -3
6)
The limit function is expressed as [tex]\lim_{x \to 3} (x^{2} +3x - 1)[/tex].
So, when x = 3, the limit is:
L = 3² + 3 ( 3 ) - 1
L = 9 + 9 - 1
L = 17
7)
The limit function is expressed as [tex]\lim_{x \to 4} \frac{(x^{2} -16)}{x-4}[/tex].
So, when x = 4, the limit is simplified as:
[tex]\lim_{x \to 4} \frac{(x^{2} -16)}{x-4}=\lim_{x \to 4} \frac{(x-4)(x+4)}{x-4}[/tex]
[tex]\lim_{x \to 4} \frac{(x-4)(x+4)}{x-4}=\lim_{x \to 4} (x+4)[/tex]
L = 4 + 4
L = 8
8)
The limit function is expressed as [tex]\lim_{x \to 0} \frac{(x^{2} -2x)}{x^{4} }[/tex].
So, when x = 0, the limit is simplified as:
L = 0/0 and the limit does not exist.
Hence, the limits are solved.
To learn more about property of limits:
https://brainly.com/question/30339385
#SPJ4
HELP ME please .. I really need it lol
Answer:
C
Step-by-step explanation:
The absolute value function always returns a positive value
However, the expression inside the bars can be positive or negative
| 3 | = 3 and | - 3 | = 3, hence the solution of
| x | = 3 is x = ± 3
Extending this to
| x² - 4 | = 3, then
| x² - 4 | = 3 and | - (x² - 4) | = 3
x² - 4 = 3 ; - (x² - 4) = 3 → C
Answer:
C
Step-by-step explanation:
[tex]|x^2-4|=3[/tex]
Before we say what this implies, we need to know that |-1|=1 and |1|=1.
So what I'm saying is:
[tex]|-(x^2-4)|=|-1 \cdot (x^2-4)|=|-1| \cdot |x^2-4|[/tex]
[tex]=|x^2-4|[/tex].
So [tex]|x^2-4|=3[/tex] implies:
[tex](x^2-4)=3[/tex] or [tex]-(x^2-4)=3[/tex].
If sine theta equals three over four, what are the values of cos θ and tan θ?
cosine theta equals plus or minus square root of seven over four, tangent theta equals plus or minus two times square root of seven over seven
cosine theta equals plus or minus seven over four, tangent theta equals negative three over seven
cosine theta equals plus or minus square root of seven over 4, tangent theta equals plus or minus three over seven
cosine theta equals plus or minus seven over four, tangent theta equals negative one over seven
Answer:
Part 1) [tex]cos(\theta)=(+/-)\frac{\sqrt{7}}{4}[/tex]
cosine theta equals plus or minus square root of seven over 4
Part 2) [tex]tan(\theta)=(+/-)\frac{3}{\sqrt{7}}[/tex]
tangent theta equals plus or minus three over square root of seven
or
[tex]tan(\theta)=(+/-)3\frac{\sqrt{7}}{7} [/tex]
tangent theta equals plus or minus three times square root of seven over seven
Step-by-step explanation:
we have that
The sine of angle theta is equal to
[tex]sin(\theta)=\frac{3}{4}[/tex]
Is positive
therefore
The angle theta lie on the I Quadrant or in the II Quadrant
Part 1) Find the value of the cosine of angle theta
Remember that
[tex]sin^{2} (\theta)+cos^{2} (\theta)=1[/tex]
we have
[tex]sin(\theta)=\frac{3}{4}[/tex]
substitute and solve for cosine of angle theta
[tex](\frac{3}{4})^{2}+cos^{2} (\theta)=1[/tex]
[tex]cos^{2} (\theta)=1-(\frac{3}{4})^{2}[/tex]
[tex]cos^{2} (\theta)=1-\frac{9}{16}[/tex]
[tex]cos^{2} (\theta)=\frac{7}{16}[/tex]
[tex]cos(\theta)=(+/-)\frac{\sqrt{7}}{4}[/tex]
cosine theta equals plus or minus square root of seven over 4
Part 2) Find the value of tangent of angle theta
we know that
[tex]tan(\theta)=\frac{sin(\theta)}{cos(\theta)}[/tex]
we have
[tex]sin(\theta)=\frac{3}{4}[/tex]
[tex]cos(\theta)=(+/-)\frac{\sqrt{7}}{4}[/tex]
substitute
[tex]tan(\theta)=\frac{\frac{3}{4}}{(+/-)\frac{\sqrt{7}}{4}}[/tex]
[tex]tan(\theta)=(+/-)\frac{3}{\sqrt{7}}[/tex]
tangent theta equals plus or minus three over square root of seven
Simplify
[tex]tan(\theta)=(+/-)3\frac{\sqrt{7}}{7} [/tex]
tangent theta equals plus or minus three times square root of seven over seven
The correct values for cosine and tangent when sine theta equals 3/4 are, cosine theta equals plus or minus 3/4, and tangent theta equals plus or minus 3/7. These values are found using the Pythagorean identity and the definitions of tangent in terms of sine and cosine.
Explanation:To solve for cos θ and tan θ when given that sin θ = ¾, one can use the Pythagorean identity, which states that sin2 θ + cos2 θ = 1. Substituting the known value of sin θ, we get (¾)2 + cos2 θ = 1. Solving this equation yields cos2 θ = 1 - (¾)2 = ¹⁄16, so cos θ is either the positive square root of ¹⁄16 or its negative counterpart. Since the square root of ¹⁄16 is ³⁄4, cos θ can be either ³⁄4 or -³⁄4.
For tan θ, which is defined as sin θ/cos θ, we use the positive and negative values found for cos θ. Therefore, tan θ can be 3/4 divided by ³⁄4, which simplifies to ³⁄7 or, when using the negative cosine value, tan θ will be -³⁄7.
Evaluate: ƒ(x) = 3 − 4x and ƒ(-5)
Answer:
23
Step-by-step explanation:
f(x)=3 − 4x
Let x=-5
f(-5) = 3-4(-5)
= 3 -(-20)
= 3+20
=23
The endpoints of a segment are (4, 2) and (-2, 2). What are the endpoints of the segment after it has been translated 6 units
down?
A. (4, -4), (-2,-4)
B. (4, -4), (-2,2)
C. (4.6). (-2, 6)
D. (4.8). (-2,8)
Answer:
A
Step-by-step explanation:
A translation of 6 units down means subtract 6 from the original y- coordinates while the x- coordinates remain unchanged, that is
(4, 2 ) → (4, 2 - 6 ) → (4, - 4 )
(- 2, 2 ) → (- 2, 2 - 6 ) → (- 2, - 4 )